DOES MEMORABLE TOURIST EXPERIENCE AND PRICE INFLUENCE TOURIST SATISFACTION ON HALAL TOURIST DESTINATION - Dessy Nurrohmah; Devy Widya Apriandi (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
Tourism is an important priority because this sector is able to bring various benefits and can attract tourists from various regions. D'castello tourism is a tourist attraction in Subang district which has the beauty of a building in the style of the Moscow Kremlin Fortress in Russia. The focus of this research is those who have visited the D'castello Subang tourist attraction. This research aims to determine the effect of Memorable Tourist Experience and Price on Tourist Visit Satisfaction at the D'castello Subang tourist attraction. The method used in this research is the explanatory survey method, with descriptive and verification research types. The population of this research is Subang and non-Subang people who have visited the D'castello Subang tourist flora. The sampling technique used was the Probablity Sampling technique with the Stratified random sampling method. Data collection was carried out by distributing questionnaires to 120 respondents who had visited the D'castello Subang tourist flora. The results of this research show that Memorable Tourism Experience and Price influence Tourist Visit Satisfaction. As many as 62.4% of the variables of Tourist Visit Satisfaction are influenced by Memorable Tourism Experience and Price. Meanwhile, the remaining 37.6% is explained by other variables that are not in this study. Suggestions for future researchers are to add variables and develop research and use different research methods so that research results are more varied.